Effects of exercise‐induced intracellular acidosis on the phosphocreatine recovery kinetics: a 31P MRS study in three muscle groups in humans. (23rd May 2013) - Layec, Gwenael; Malucelli, Emil; Le Fur, Y.; Manners, David; Yashiro, Kazuya; Testa, Claudia; Cozzone, Patrick J.; Iotti, Stefano; Bendahan, David
Abstract : Little is known about the metabolic differences that exist among different muscle groups within the same subjects. Therefore, we used 31 P‐magnetic resonance spectroscopy ( 31 P‐MRS) to investigate muscle oxidative capacity and the potential effects of pH on PCr recovery kinetics between muscles of different phenotypes (quadriceps (Q), finger (FF) and plantar flexors (PF)) in the same cohort of 16 untrained adults. The estimated muscle oxidative capacity was lower in Q (29 ± 12 mM min ‐1, CVinter‐subject  = 42%) as compared with PF (46 ± 20 mM min ‐1, CVinter‐subject  = 44%) and tended to be higher in FF (43 ± 35 mM min ‐1, CVinter‐subject  = 80%). The coefficient of variation (CV) of oxidative capacity between muscles within the group was 59 ± 24%. PCr recovery time constant was correlated with end‐exercise pH in Q ( p  < 0.01), FF ( p  < 0.05) and PF ( p <0.05) as well as proton efflux rate in FF ( p  < 0.01), PF ( p  < 0.01) and Q ( p  = 0.12). We also observed a steeper slope of the relationship between end‐exercise acidosis and PCr recovery kinetics in FF compared with either PF or Q muscles. Overall, this study supports the concept of skeletal muscle heterogeneity by revealing a comparable inter‐ and intra‐individual variability in oxidative capacity across three skeletal muscles in untrained individuals. These findings also indicate that the sensitivity of mitochondrial respiration to the inhibition associated with cytosolic acidosis is greater in the finger flexor muscles compared with locomotor muscles, which might be related to differences in permeability in the mitochondrial membrane and, to some extent, to proton efflux rates. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The metabolic variability across muscles cannot be fully explained by differences in fiber type or the chronic load experienced by the quadriceps, finger and plantar flexor muscles, thereby pointing to intrinsic metabolic differences and supporting the concept of skeletal muscle heterogeneity. Finger flexor muscles also exhibit a greater sensitivity to the inhibitory effect of cytosolic acidosis on mitochondrial respiration, which could be related to a greater permeability of the mitochondrial membrane and, to some extent, to proton efflux rates.